Significant tricuspid regurgitation is associated with adverse outcomes in patients with transthyretin amyloid cardiomyopathy - Decotto, Santiago (2024)
Objectives. Patients diagnosed with transthyretin amyloid cardiomyopathy (ATTR-CM) often experience poor outcomes due to the development of heart failure (HF). Tricuspid regurgitation (TR) has been found to be correlated with adverse outcomes in patients with HF. This study aims to assess whether the presence of significant TR is associated to adverse cardiac outcomes in patients diagnosed with ATTR-CM. Materials and methods. Retrospective study of ATTR-CM patients enrolled in the Institutional Registry of Amyloidosis (NCT01347047). Patients were categorized based on the presence of significant TR (moderate or severe according to current guidelines criteria) or absence of significant TR. All patients were followed up for 2 years to assess the incidence of the composite outcome of death or HF hospitalization. Results. A total of 93 ATTR-CM patients were included. The mean age at diagnosis was 82.5 [IQR 75 - 86] years, 86% were male, and the mean left ventricular ejection fraction was 52% [IQR 43 - 60]. Among them, 32.3% (n = 30) patients had significant TR. Patients with significant TR had higher NTpro-BNP values (5308 vs 2454, pg/mL, p = 0.004), and a lower left ventricular ejection fraction (44 vs. 56%, p = 0.0002) compared to patients without significant TR. The incidence of the primary outcome was higher in patients with significant TR (77% vs. 30%, p<0.001). In a multivariate Cox regression analysis, only NTpro-BNP, as a numerical variable (HR 1.00, 95% CI 1.00005-1.0002, p = 0.001), and significant TR (HR 2.23, 95% CI 1.12-4.42, p=0.021) were independently associated with the composite outcome of death or HF hospitalization. Conclusions. In patients diagnosed with ATTR-CM, the presence of significant TR was associated with worse outcomes.